The development of android-based computer and basic network learning media - Aisah Sunari Sansi; Faiza Rini; Thomson Mary; Tee Tze Kiong (Researcher and Lecturer Society, 2023)
This study aims to produce valid and practical android-based learning media. Learning methods that are not yet optimal and there is no Android-based learning media can be used as a supporting medium for the learning process. This study used the Research and Development (R&D) method with the ADDIE development model. The subjects of this study were 20 students as a sample. Data collection techniques using a questionnaire with a Likert scale. The results of this study indicate that the average value of the media expert's validity test is 0.68 with the valid category and the material expert is 0.67 with the valid category. For the practicality test on the teacher's response it reached 83.33% in the very practical category and for student responses it reached 90.92 % in the very practical category . Based on the assessment along with input from media experts and material experts as well as the results of field trials of Android-based learning media, it is feasible to use.